DETEKSI Pseudomonas syringae pv. glycinea (PSG) MENGGUNAKAN ANTIBODIPOLIKLONAL DAN NCM-ELISA - Suryadi, Y; Machmud, M (Research Center for Biology-Indonesian Institute of Sciences, 2006)
Soybean bacterial blight is an important disease of the soybean crop. Since resistant cultivars are lacking, the disease is difficult to control, hence early detection and proper diagnosis as well as good knowledge on epiphytotic of the disease are important aspects for successful disease control.A serological technique, particularly the Enzyme-linked Immunosorbent Assay (ELISA) is an effective technique for detection and identification of plant pathogens. The objective of the research was to obtain polyclonal antibodies (PAbs) and use of NCM-ELISA for detection PSG. Soybean plant samples showing symptoms of soybean bacterial blight were collected from the fields and used for antigen sources. Isolation and production of PSG antigen was done using Kings B Agar medium. Immunizations of white New Zealand rabbits were done to produce antibodies to PSG. Yield of PAb-PSG was indicated by antisera titers ranging from 160 to 1280. Intravenous immunization produced more titer than that of intramuscularly. NCM-ELISA was used for detection of PSG from plant samples. It was applicable for detection of PSG from plant samples in relatively short time and limit detection of 10